Enhanced Productivity of Greengram Through Cluster Front Line Demonstration in Jaipur District of Rajasthan - Babu Lal Yadav,; Irfan Khan,; Shaitan Singh Rathore,; Mudit Gupta, (Annals of Agricultural Research, 2023)
Cluster front line demonstration (CFLDs) on greengram was conducted by Krishi Vigyan Kendra, Chomu (Tankarda) District- Jaipur (Rajasthan) during Kharif 2019 and 2020 and the demonstration conducted in five different villages namely Mandor, Trilokpura, Bhadipura, Mansar and Mokhampura in Jaipur district with total number of demonstrations of 100 and an area of 40 ha. The new technologies consist of improved varieties, seed treatment, weed management, nutrient management and plant protection measures. The results demonstrated that the maximum average yield was 7.95q/ha in demonstration plot and the minimum yield was 6.10 q/ha in the farmers practice. The highest average net return (Rs.41,790/ha) was obtained in the demonstration plot compared to farmers’ practice (Rs.30,606/ha). The average B:C ratio was 2.80 in demonstrated plot and the lowest was found 2.36 in farmer practice. The average yield increase percent was 30.54 in demonstration plot as compared to farmer practice. The technology gap was ranged from 2.31 to 6.03 q/ha, extension gap was 1.40 to 2.09q/ha and technology index was 23.10 to 43.07 percent.